Synthesis, Molecular Docking Study and Cytotoxicity Evaluation of some Quinazolinone Derivatives as Nonclassical Antifolates and Potential Cytotoxic Agents - Mohammed Abdulameer Oleiwi; Munaf H. Zalzala (College of Pharmacy University of Baghdad, 2022)
Abstract A series of new 4(3H)-quinazolinone derivatives (S1-S4) were synthesized and characterized   by FTIR,1HNMR and 13CNMR .Their cytotoxic activity against a set of human cancer cell lines MCF-7 (breast) and A549 (lung) was evaluated using MTT assay. To detect their selectivity toward cancer cells, the compounds were also tested against epithelial cells derived from normal human fibroblast (NHF). Methotrexate (MTX) was used as a reference for comparison . All the tested compounds exhibited toxicity against the normal cells lower than cancer cells. All the tested compounds displayed higher cytotoxicity against lung cancer cell line (A549) than MTX with the most potent one is compound S2 (IC50: 5.73 µM). Among the tested compounds, compound S1 exhibited the highest antitumor activity against MCF-7cell line (IC50: 3.38 µM) compared to MTX (IC50: 27.32 µM). The binding modes of the synthesized compounds with the target proteins (DHFR and TS) were investigated by molecular docking studies using GOLD software.